Design of rate-compatible low-density parity-check codes for type-II hybrid ARQ systems - WANG Dan; WANG Xin-mei (Tongxin xuebao)
The design of powerful rate-compatible low-density parity-check codes（RC-LDPC）was constructed in zigzag structure for type-II hybrid ARQ systems.The generalized PEG algorithm was used in the process of constructing RC-LDPC codes to improve the performance of the proposed codes.Simulation results show that based on constructed RC-LDPC codes,a type-II hybrid ARQ system can achieve efficient throughput.In addition,very low-complexity encoding and decoding rules can be implemented due to the overall zigzag structure of these RC-LDPC codes.